PEMBUATAN NANOSILIKA GEL DARI SILIKA ABU SEKAM PADI - Rahman, Arif (JFT : Jurnal Fisika dan Terapannya, 2018)
The research has been carried out under the title of the Making of Nanosilica Gel from Silica of Rice Hulk Ash. This study aims to determine the characteristics of the resulting silica gel and the ratio of moisture content and its adsorbsity with silica gel of the market product is Kiesel Gel 60 GF254. There have been many studies showing that rice husk contains silica of 87-97%. The silica extraction process of the rice husk uses a reflux method extraction process. Meanwhile, the process of making silica nanoparticles using ultrasonic milling method. Ultrasonic milling method is a method to solve particles by utilizing ultrasonic waves which will produce cavitation phenomena. Based on the research, it can be concluded that rice husk used in this research has silica content of 93,46%. The resulting silica gel was divided into three with each different treatment are silica gel without sonication process (TN), silica gel with sonication process for 60 minutes (N 60) and for 120 minutes (N 120). The silica gel has particle size, morphology, elemental content, lattice parameters, crystalline form, crystal phase and different moisture content and adsorption capability. According to the research that has been done, kiesel gel 60 GF254 has water content value and adsorption ability respectively that is 0.045% and 0.1569 gr / ml. Silica gel having water content value and adsorption ability which closest to kiesel gel 60 GF254 are N 60 with moisture value of 0.035% and N 120 with an adsorption capacity of 0.1279 gr / ml. However, silica gel having water content and adsorption ability were TN with moisture value and adsorption ability of 0.2% and 0.2025 gr / ml, respectively..Â Key Words: Rice husk, silica, nanosilika, moisture content, adsorption.